Dive in Learning Civics in Elementary Schools Through LKS Based Activities and Experiences Meaningful - Grace Gita Terulin Br Tarigan (International Journal of Students Education, 2024)
Worksheet student is learning media tools used by teachers for send material teaching, information, or message important to student in the learning process. This study aim for elaborate development sheet work student with hope can give outlook new for improve the learning process takes place in order to become more effective than previously. Method used is studies library, where data is collected with understand and learn various literature related this study. Research result show that development tool learning is very important in implementation of the learning process teach for facilitate sheet work based students activity and meaning, so student can develop ability think critical in PK learning and giving provisions for the future they. With the development of interesting and systematic worksheets is expected learning Civics can become more effective and interesting for participant educate, help they in understanding material as well as development Skills active and creative .Can concluded that development of PK -based worksheets activity and meaning expected can increase learning for student in increase results study